5(2-b)=-3(b-3)

Simple and best practice solution for 5(2-b)=-3(b-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2-b)=-3(b-3) equation:


Simplifying
5(2 + -1b) = -3(b + -3)
(2 * 5 + -1b * 5) = -3(b + -3)
(10 + -5b) = -3(b + -3)

Reorder the terms:
10 + -5b = -3(-3 + b)
10 + -5b = (-3 * -3 + b * -3)
10 + -5b = (9 + -3b)

Solving
10 + -5b = 9 + -3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '3b' to each side of the equation.
10 + -5b + 3b = 9 + -3b + 3b

Combine like terms: -5b + 3b = -2b
10 + -2b = 9 + -3b + 3b

Combine like terms: -3b + 3b = 0
10 + -2b = 9 + 0
10 + -2b = 9

Add '-10' to each side of the equation.
10 + -10 + -2b = 9 + -10

Combine like terms: 10 + -10 = 0
0 + -2b = 9 + -10
-2b = 9 + -10

Combine like terms: 9 + -10 = -1
-2b = -1

Divide each side by '-2'.
b = 0.5

Simplifying
b = 0.5

See similar equations:

| 9a-7=29 | | 3b^2+26b+48=0 | | 167+19x+16x=1132 | | 4x-2(x-8)=2(x+1)+5 | | 4n+2=3n | | 5x+8y=6n | | -5n=-30 | | 3x+12=9x+9 | | 3x+3/2(2x-1)=2 | | -5x-12=3x-6x | | -5=-30 | | 3q+12=9q+9 | | 23x-12=33 | | -14+6b+7-2b=1+56 | | n+1/7=2/3 | | 3x+17=14x+6 | | 5.3x-7=2.3+5 | | 10-(x+7)=5 | | 98.4-0.365t=102.05 | | 3-3m-3m-8p-3p= | | (6x-3)+1=-10 | | s^2+3s-18= | | 241.00-130.00= | | 14x+7=-1x | | -18x-161=-11-98 | | 8.2=15-(2x+3) | | 9-4z=51 | | 4.824-5= | | 12-4x=-2x-2 | | 8+a=2a-2-3a | | 4(y-1)=24 | | 144554=2141534 |

Equations solver categories